An Evaluation of Software Project Risk Management in South Africa - De Wet, B. (South African Journal of Industrial Engineering, 2013)
Global research indicates that the success rate of software projects worldwide is currently very low, and has been low for the past few decades. The application of risk management has improved the success rate of software projects in the developed world. This study investigated whether the success rate of software projects in South Africa is also low, and whether risk management might improve these success rates. The results indicate that the average success rate of software projects in South Africa is indeed very low, and that software projects in South Africa often experience the same risks as in the developed world. It was also found that, where risk management is applied, software projects produce better results than software projects with no risk management. The majority of South African software companies use ad hoc internally developed risk management procedures rather than formalised procedures.